Unlocking the Secret to Customer Happiness: A Deep Dive Into the Satisfaction and Loyalty Levels of Pia Cap Mangkok Purchasers in Malang - Dinda Tasya febrianti,; Anas Tain,; Gumoyo Mumpuni Ningsih, (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2023)
In today's highly competitive business landscape, analyzing customer satisfaction and loyalty is a critical strategy for companies to stay ahead. This study investigated the level of customer satisfaction and analyzed consumer loyalty towards Pia Cap Mangkok, a popular food brand in Malang, Indonesia. A total of 91 respondents were selected using purposive sampling, and data was collected through observation, interviews, and documentation methods. The study used both primary and secondary data to evaluate the level of customer satisfaction and analyze consumer loyalty. Customer satisfaction was measured through product and service attributes using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA), and the study found that Pia Cap Mangkok scored 74.44% in the satisfied criteria. The IPA technique identified attributes that must be maintained and improved, including taste, pia flavor, atmosphere, cleanliness, swift and friendly waiter service, efficient order process, room decoration, and waiter appearance. Moreover, the Loyalty Pyramid was used to analyze consumer loyalty, and the study found that 85% of the buyers are satisfied, 85% like the brand, 58% are committed buyers, 28% are switchers, and 16% are habitual buyers. The study provides valuable insights for Pia Cap Mangkok to develop effective marketing strategies to maintain its customer base and attract new customers.